Cattle ranchers and deforestation in the Brazilian Amazon: Production, location, and policies. (May 2021) - Skidmore, Marin Elisabeth; Moffette, Fanny; Rausch, Lisa; Christie, Matthew; Munger, Jacob; Gibbs, Holly K.
Highlights: We present a statistical analysis of 113, 000 cattle suppliers in the Amazon. 22 factors shed light on how supply chain characteristics relates to deforestation. Properties with deforestation sell fewer cattle and earlier in the supply chain. They are located in remote locations and have a high percent of remaining forest. Our findings can be used to monitor properties where deforestation is more likely. Abstract: Deforestation for cattle production persists in the Brazilian Amazon despite ongoing efforts by the public and private sectors to combat it. The complexity of the cattle supply chain, which we describe in depth here, creates challenges for the landmark Zero-Deforestation Cattle Agreements in particular and for enforcement of deforestation policies in general. Here, we present a holistic analysis that is increasingly relevant as the number of policies, initiatives, and markets affecting the region increases. We provide the first property-level analysis of which ranchers decided to deforest in the last decade and identify the characteristics that are most related to deforestation. We rely on newly available animal transit and property boundary data to examine 113, 000 properties in the three major cattle-producing states in the Brazilian Amazon. We consider characteristics related to a property's role in the supply chain, location, land characteristics, and the policy environment. We find that deforestation is most likely to occur on properties that sell fewer cattle and earlier in the supply chain, are located in remote locations, and have a high percent of remaining forest. Our results can be used to improve enforcement of existing policies by targeting resources to properties and location where deforestation is more likely.